Provisional Stenting Techniques Using A Novel Modified Jailed Balloon - Muhammad Syukri; Ivan Mahendra; Hadi Zulkarnain; Denada Florencia Leona (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Coronary bifurcation lesions are frequently found; account for one-fifth of all Percutaneous Coronary Interventions (PCI), and are considered as complex cases to treat. The provisional stenting strategy is thought of as the stenting of choice for most coronary bifurcation lesions. Still, it has a risk of side branch (SB) occlusion after the main vessel (MV) stenting. Several strategies have been proposed to overcome this challenge. Jailed balloon technique (JBT), first proposed by Burzotta et al. in 2010 was a more recent modification of jailed wire technique (JWT) to further decrease the risk for SB occlusion during crossover stenting in bifurcation lesion. Since then, certain modifications had been tested to the conventional jailed balloon technique to maximize SB protection during the provisional stenting strategy. We tried to make a mini case series of 6 patients with application of jailed ballon technique with some modifications in bifurcation lesion with provisional stenting strategy and evaluate its efficacy and safety, with quite satisfying results. Our novel JBT technique had some different characteristics from previous JBT techniques and aimed at simplifying the procedure while preserving side branch during crossover stenting.